2007
DOI: 10.1007/s10336-007-0208-3
|View full text |Cite
|
Sign up to set email alerts
|

Habitat utilisation, feeding tactics and age related feeding efficiency in the Caspian Gull Larus cachinnans

Abstract: The feeding behaviour of the Caspian Gull Larus cachinnans was analysed in southern Poland in 2001. During the pre-breeding period, most birds foraged on a refuse dump and some foraged in a river valley. During incubation, similar numbers of birds foraged on fishponds, gravel pits and the refuse dump. During the chick-rearing period, fishponds were the most important foraging grounds. The foraging success of three main foraging tactics was analysed: digging on refuse, fishing and kleptoparasitism. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 23 publications
(32 reference statements)
2
30
1
1
Order By: Relevance
“…The gulls captured fish varying between 5 and 47 cm (Gwiazda 2004;Gwiazda et al 2011, Skórka unpublished). The size of fish captured does not differ between adult, immature and juvenile birds (Skorka and Wojcik 2008).…”
Section: Study Speciesmentioning
confidence: 87%
See 2 more Smart Citations
“…The gulls captured fish varying between 5 and 47 cm (Gwiazda 2004;Gwiazda et al 2011, Skórka unpublished). The size of fish captured does not differ between adult, immature and juvenile birds (Skorka and Wojcik 2008).…”
Section: Study Speciesmentioning
confidence: 87%
“…First, in larger settlements gulls may use refuse-tips as foraging habitat. Caspian gulls, however, gather at refuse tips in larger numbers only in late autumn and winter (Skorka and Wojcik 2008). The second possibility is that humans have direct negative effect on abundance, for example in waterbodies surrounded by dense settlements more people visiting/walking/fishing may disturb foraging birds (Fernández-Juricic and Tellería 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the reservoir under study, numerous fish were found at nests of Caspian gulls, indicating that this was a major food for them. Skórka and Wójcik (2008) clearly showed that this species foraged mostly on fish farms and hunted for fish, while the proximity of fish farms is one of the major factors affecting its successful colonization of inland reservoirs (Lenda et al 2010). Therefore, it is possible that the availability of alternative food resources in the form of the fish, bred in Poland's numerous fish farms, may be a factor that limits the direct predatory impact of this invasive gull on native waterbirds.…”
Section: Discussionmentioning
confidence: 99%
“…Foraging efficiency (energy gained per unit effort) increases with age and experience in many species (Galbraith et al 1999, Daunt et al 2007, Skorka & Wojcik 2008, potentially because an individual's ability to find and handle prey improves with experience (Orians 1981, Galbraith et al 1999. In central place foragers, experience may influence the point at which the individual decides to return to their offspring.…”
Section: Introductionmentioning
confidence: 99%